2020
DOI: 10.1007/s10803-020-04560-x
|View full text |Cite
|
Sign up to set email alerts
|

Is It Fear? Similar Brain Responses to Fearful and Neutral Faces in Infants with a Heightened Likelihood for Autism Spectrum Disorder

Abstract: Individuals with autism spectrum disorder (ASD) show atypical processing of facial expressions. Research with autistic toddlers suggests that abnormalities in processing of spatial frequencies (SFs) contribute to such differences. The current event-related-potential (ERP) study investigated differences between 10-month-old infants with high- and low-likelihood for ASD in SF processing and in discrimination of fearful and neutral faces, filtered to contain specific SF. Results indicate no group differences in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…This special issue includes four studies (Hatch et al 2020;Lorenzo et al 2020;Stenberg et al 2020;Tanner and Dounavi 2020) that provide new insight on early emerging symptoms. This is a critical area of investigation because the age of diagnosis in epidemiological samples is still 3-5 years of age (Baio et al 2018;Fountain et al 2011;Mandell et al 2010;Shaw et al 2020).…”
Section: Early Manifestations and Outcomes Of Children Identified Earliermentioning
confidence: 99%
See 2 more Smart Citations
“…This special issue includes four studies (Hatch et al 2020;Lorenzo et al 2020;Stenberg et al 2020;Tanner and Dounavi 2020) that provide new insight on early emerging symptoms. This is a critical area of investigation because the age of diagnosis in epidemiological samples is still 3-5 years of age (Baio et al 2018;Fountain et al 2011;Mandell et al 2010;Shaw et al 2020).…”
Section: Early Manifestations and Outcomes Of Children Identified Earliermentioning
confidence: 99%
“…Hatch and colleagues examined children at various timepoints between 6 and 36 months of age and found impaired response to name to be a general marker for ASD or ADHD early in the developmental period, but specific to ASD in older toddlers. Lorenzo et al (2020) investigated another potential early marker for ASD, examining differences between 10-month old toddlers processing of spatial frequencies and discrimination between fearful and neutral facial expressions. Stenberg et al (2020) assessed cognitive, functional language and symptom severity in children that were invited to participate in the Norwegian Mother, Father and Child (MoBa) study's sub-study: the Autism Birth Cohort (ABC) study.…”
Section: Early Manifestations and Outcomes Of Children Identified Earliermentioning
confidence: 99%
See 1 more Smart Citation
“…The second relevance of the SF content is that studies in older children and adults suggest that specific SF content is used to process emotional expressions (Jeantet et al, 2018). Event-related potential (ERP) studies revealed that although adults show differential responses when only LSF are presented (Pourtois et al, 2005;Vlamings et al, 2009), 7-and 10-month-old infants do this when only HSF are presented (van den Di Lorenzo et al, 2021;Jessen & Grossmann, 2017). No studies have investigated the role of specific SFs in emotional face processing in infants below 7 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there are even suggestions for an interaction between the quality of interaction and the role of the SF content. While most previous studies investigated either spatial frequency content or parent-child interaction in relation to emotional face processing, there are a few studies in older children (10-month-old infants: Di Lorenzo et al, 2021;3-to 4-year-olds: Vlamings et al, 2010) indicating that these two factors interact. More specifically, these studies investigated children at familial high likelihood for or diagnosed with autism spectrum disorder (ASD), a disorder characterized by atypical social interaction (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%